A STATE OF THE ART ON THE VALUATION OF PROFESSIONALS IN EARLY EARLY EDUCATION TEACHING (Interdisciplinary Studies Journal, 2024)
The text presents a study of the art of academic productions on the appreciation of Early Childhood Education (EI) teaching professionals, considering remuneration and career, and aims to map, discuss and present what has been developed in postgraduate programs , in education in Brazil, on this topic, from 2010 to 2022. This is a Systematic Review study using a qualitative and quantitative approach, of an exploratory and documentary nature. Our research source was the Capes Theses and Dissertations Bank. Only eight works were found: six dissertations and two theses. We organize a table considering the year of publication, linked institution, objectives, methodology, research results. We understand that there are few studies on the topic, which are concentrated in the southern and southeastern regions of Brazil. There is an urgency for a greater understanding of this field, and a need for research that considers all regions of Brazil, especially the northeast region. We noticed a differentiation in the career of the EI teacher, in relation to other basic education teachers (work hours, composition, etc.), and a fluctuation in the remuneration of the EI teacher (bonus and gratification).
Keywords: Child Education; Professional Valuation of Teaching; Career and Remuneration